CD163 Identifies Perivascular Macrophages in Normal and Viral Encephalitic Brains and Potential Precursors to Perivascular Macrophages in Blood - Kim, Woong-Ki (American Society for Investigative Pathology, 2006)
Perivascular macrophages are uniquely situated at the intersection between the nervous and immune systems. Although combined myeloid marker detection differentiates perivascular from resident brain macrophages (parenchymal microglia), no single marker distinguishes perivascular macrophages in humans and mice. Here, we present the macrophage scavenger receptor CD163 as a marker for perivascular macrophages in humans, monkeys, and mice. CD163 was primarily confined to perivascular macrophages and populations of meningeal and choroid plexus macrophages in normal brains and in brains of humans and monkeys with human immunodeficiency virus or simian immunodeficiency virus (SIV) encephalitis. Scattered microglia in SIV encephalitis lesions and multinucleated giant cells were also CD163 positive. Consistent with prior findings that perivascular macrophages are primary targets of human immunodeficiency virus and SIV, all SIV-infected cells in the brain were CD163 positive. Using fluorescent dyes that definitively and selectively label perivascular macrophages in vivo, we confirmed that dye-labeled simian perivascular macrophages were CD163 positive and able to repopulate the central nervous system within 24 hours. Flow cytometric studies demonstrated a subset of monocytes (CD163(+)CD14(+)CD16(+)) that were immunophenotypically similar to brain perivascular macrophages. These findings recognize CD163(+) blood monocytes/macrophages as a source of brain perivascular macrophages and underscore the utility of this molecule in studying the biology of perivascular macrophages and their precursors in humans, monkeys, and mice.